Measuring Determinants of Time Deposit in The Commercial Banks in Nepal - Raghu Bir Bista; Priyanka Basnet (Yayasan Ahmar Cendekia Indonesia, 2022)
Time deposit is one of major source of liquidity of the commercial bank to maintain money supply to the demand of business and household sector. In this context, an interesting query is the determinants of time deposit. This paper measures the determinants of time deposit in the commercial banks of Nepal based on 15 years’ time series data sets from 2000-01 to 2017-18 of the sample commercial banks published by the central bank of Nepal. Using descriptive statistics and multiple regression models as the analytical tools, the paper has found fluctuating trend of liquidity in the commercial banks but inclining trend of external and internal variables including GDP, Deposit, Capital, Size of Bank, remittance and public debt. In this trend, the liquidity of the commercial banks depends significantly on time deposit and remittance inflow. Besides, the positive trend of time deposit from 1994-95 to 2017-18 has caused the positive trend of total deposit from 1994-95 to 2017-18. Additionally, the paper has found that GDP per capita, US exchange rate, interest rate and the branch of the bank are positively and significantly determinants to the time deposit of the commercial bank but inflation rate is negatively and determinant with significance. The internal variables are more determinants than the external variables to the time deposits. It is clear that time deposit is a reliable and long-term source to main the bank liquidity of the commercial bank for their financial stability and performance depends on more the internal variables than the external variables. Therefore, the commercial bank should reform as mentioned in the monetary policy and money market dynamics to improve the competitiveness and smartness of bank policy including interest rate policy and branch of the commercial banks for effective mobilization of the scattered small resources all over the country for higher rate of capital formation, investment, and economic growth